Entre a devastação e a conservação: uma história ambiental da Mata do Buraquinho - Paraíba (1585 - 2014) - Menezes, Danilo Wilson Lemos (2022)
The objective of this research was to analyze the historical process characterized by the relationships that past societies established with nature in the forest territory known today as Mata do Buraquinho, from 1585 to 2014, elaborating a historical and cartographic narrative of the relationships between societies and natures in this geographic space. We mainly use, as a theoretical scope, in an interdisciplinary perspective of approach, Environmental History; the idea of a Latin American Anthropocene as a historical period marked by colonial processes and; the concepts of historical roughness, landscape, space, territory, four-dimensionality and other concepts of Geography. The narrative was elaborated after the analysis and interpretation of the historical sources, constituted essentially in archives, collections and in the field, making up a diverse and wide documentary collection. In order to conduct a critical interpretation of the sources, we used, whenever necessary, the Evidence Method and the concepts of Cartographic Silence, Silences of History and Urban Metabolism. In order to respond to the research objectives, we used as the main methodological device the analytical tool of the three dimensions of Environmental History (the reconstitution of natural landscapes, the material relationships and the subjective relationships between society and nature), in order to enable the understanding of the events and narrative construction. What the research results showed us is that this Atlantic Forest remnant is a predominantly secondary, anthropogenic and recently regenerated forest, whose intense anthropization stopped just a few decades ago. These qualities, therefore, that recurrently attribute it, as a ‘natural’ remnant of the Atlantic Forest, a ‘native’ forest or as possessing a supposedly ‘original’ vegetation, need to be revised or, at least, deeply relativized and problematized. We were able to confirm our assumptions and hypotheses regarding the complexity of the relationships established between the societies that were there and the natures that the Mata do Buraquinho culturally represented in different historical moments. Manichean elaborations cannot account for the historical process of Mata do Buraquinho, which is not an obvious result of a preservationist or conservationist project, nor can it be explained as a protected remnant, the happy exception of a process of generalized devastation. Although devastation processes predominated in the general panorama, preservation and devastation events were almost always present, one or the other prevailing in certain circumstances and conjunctures. Sometimes in dialogue, sometimes in contradiction and, in certain events, in deep confusion, making even their distinction difficult.